EFFECT OF SAUROPUS ANDROGYNUS LEAVES EXTRACT (SALE) ON FAT DEPOSITION IN BROILER FED LOW PROTEIN DIETS - Santoso, U.; Kususiyah, K.; Fenita, Y. (Diponegoro University, 2013)
The present study was designed to evaluate the effect of Sauropus Androgynus Leaves Extract(SALE) on broiler chickens fed low protein diets. Eighty four mixed broiler chickens (male:female =1:1) aged 20 days were distributed to seven treatment groups as follows: 1) Broilers fed 19% proteinwithout SALE (P0); 2) Broilers fed 19% protein plus 4.5 g SALE/kg (P1); 3) Broilers fed 17% proteinplus 4,5 g SALE/kg (P2); 4) Broilers fed 15% protein plus 4.5 g SALE/kg (P3); 5) Broilers fed 19%protein plus 9 g SALE/kg (P4); 6) Broilers fed 17% protein plus 9 g SALE/kg (P5); 7) Broilers fed15% protein plus 9 g SALE/kg (P6). Experimental results showed that supplementation of Sauropusandrogynus extract to low protein diets had no effect on meat colour, haemorrhages scale in breastmeat, and fatty liver score (P>0.05), but it significantly affected haemorrhages scale in thigh meat(P<0,01), shank colour, meat taste and flavour (P<0.05). In addition, supplementation of the extractsignificantly affected meat fat content (P<0.05) and meat cholesterol content (P<0.01), but it had noeffect on meat protein content (P>0.05). It can be concluded that the leaves extract of Sauropusandrogynus supplementation at level of 9 g/kg diets normalized fat deposition in broiler chickens fedlow protein diets. SALE improved broiler meat qualities.